2015
DOI: 10.1021/es505984y
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Highly Efficient and Wide pH Electro-Fenton Oxidation System with Molecular Oxygen Activated by Ferrous–Tetrapolyphosphate Complex

Abstract: In this study, a novel electro-Fenton (EF) system was developed with iron wire, activated carbon fiber, and sodium tetrapolyphosphate (Na6TPP) as the anode, cathode, and electrolyte, respectively. This Na6TPP-EF system could efficiently degrade atrazine in a wide pH range of 4.0-10.2. The utilization of Na6TPP instead of Na2SO4 as the electrolyte enhanced the atrazine degradation rate by 130 times at an initial pH of 8.0. This dramatic enhancement was attributed to the formation of ferrous-tetrapolyphosphate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 137 publications
(69 citation statements)
references
References 36 publications
2
64
1
Order By: Relevance
“…Green synthesis of nanoparticles has received attention due to its use of environment-friendly precursors for nanoparticles synthesis with many other advantages such as economic viability, ease of production, eco-friendly nature, avoiding the use of harmful chemicals, conditions of high temperature and pressure, and the expensive instruments required for physical and chemical methods. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Microorganisms have the ability to reduce heavy metal salts to metal nanoparticles with a narrow size distribution due to the presence of various reductase enzymes. 15 In a previous report, silver nanoparticles and PbS quantum dots were synthesized by Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Green synthesis of nanoparticles has received attention due to its use of environment-friendly precursors for nanoparticles synthesis with many other advantages such as economic viability, ease of production, eco-friendly nature, avoiding the use of harmful chemicals, conditions of high temperature and pressure, and the expensive instruments required for physical and chemical methods. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Microorganisms have the ability to reduce heavy metal salts to metal nanoparticles with a narrow size distribution due to the presence of various reductase enzymes. 15 In a previous report, silver nanoparticles and PbS quantum dots were synthesized by Aspergillus sp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a research group has demonstrated the pentachlorophenol-contaminated soil can be effectively remediated by soil washing with TPP solution and the subsequent oxidative treatment of the wastewater by the ZVI/O2 system [54]. The same group also suggested a novel electro-Fenton system using Fe(II)-TPP complexes applicable for a wide pH range [55]. A sequential reduction-oxidation process using ZVI may also be useful to treat multiple organic contaminants; ZVI is first used to treat reductively-degradable organic contaminants such as perchlorinated compounds under anoxic conditions, and subsequently, by supplying O2 the residual ZVI and Fe(II) oxidatively degrade remaining organic contaminants.…”
Section: Application To Removal Of Water Contaminantsmentioning
confidence: 99%
“…4–6, where TPP represents triphosphate) . It is worthy of note that the above‐mentioned behavior has only been reported in EF systems where Fe 2+ ions are constantly released from the anode or the cathode, and in the presence of important concentrations of polyphosphate derivatives as electrolyte (50 mmol L −1 ). Therefore, the real contribution of the chemical Fe‐TPP oxidation process to the whole EF efficiency has not been conclusive.…”
Section: Introductionmentioning
confidence: 97%
“…OH oxidation and thus, diminishing the efficiency of the process ,. In the case of inorganic ligands, polyphosphate derivatives have recently emerged as potential options for Fenton‐based systems, including EF ,. Tetraphosphates and triphosphates have been reported to allow EF to operate at near‐neutral pH, not only without compromising the efficiency by .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation